Analisis Sifat Mekanis RTV Silicone Rubber dengan Variasi Silicone Oil untuk Pengembangan Injection Training Arm - Romadhon, Saeful Rofi; Ismail, Rifky; Bachtiar, Yuriz; Prawibowo, Hartanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
RTV silicone rubber is widely used in medical simulation devices because of its properties that resemble human soft tissue, especially in injection training arms that require elasticity, tensile strength, tear resistance, and adequate hardness to withstand repeated needle penetration. This study aims to evaluate the effect of adding silicone oil on the mechanical properties of type 00A RTV silicone rubber through tensile testing (ISO 37:2024), tear testing (ISO 34-1:2022), and hardness testing (ASTM D2240). Three formulations were tested, namely pure RTV, RTV + 5 phr silicone oil, and RTV + 15 phr silicone oil. The results showed that the addition of 5 phr silicone oil produced the most significant improvement in mechanical properties, with a tensile strength of 0.57 N/mm², elongation of 363.4%, tear resistance of 0.42 N/mm, and hardness of 9.3 Shore A, compared to pure RTV which only reached 0.38 N/mm², 199.26%, 0.33 N/mm, and 7.2 Shore A. Conversely, the addition of 15 phr silicone oil reduced performance due to excessive plasticization, although the hardness value still increased to 9.9 Shore A. Thus, the 5 phr silicone oil formulation is recommended as the optimal composition for realistic and economical injection training arm applications.